UV-MALDI mass spectrometry analysis of NBD-glycosphingolipids without an external matrix - Landoni, Malena (2008)
Fil: Landoni, Malena. CIHIDECAR-Departamento de Química Orgánica, Facultad de Ciencias Exactas y Naturales, Universidad de Buenos Aires, Buenos Aires; Argentina.